East and west perspective on postal voting: a study of the postal voting systems in Malaysia and the United Kingdom / Nur Syuhada Shafiee, Nur Yasmin Osman and Soraya Fadzwin Ramlee - Shafiee, Nur Syuhada; Osman, Nur Yasmin; Ramlee, Soraya Fadzwin (Faculty of Law, 2008)
The purpose of this study is to evaluate and assess the effectiveness and the integrity of postal voting in Malaysia. It specifically discusses the present process to observe whether there are any defects in the current system. In this study, several major shortcomings have indeed been identified. A comparison is made with the postal voting system in the United Kingdom to observe how it is conducted and identify the methods of dealing with the flaws in the system. With this, relevant recommendations are made and some were adopted from the postal voting system in the United Kingdom. The main reason for this would be to enhance the transparency and credibility of the postal voting system in this country. After all, a free and fair election is critical towards ensuring that Malaysians have control over their own vote, and that the country is governed in a responsible, competent and accountable manner.